STRATEGI PENDIDIKAN BERKELANJUTAN DI TENGAH GELOMBANG DISRUPSI - Resti Herliawati; Revalina Julianti Abdul Fatah; Ichsan Fauzi Rachman (JOURNAL SAINS STUDENT RESEARCH, 2024)
In today's era of disruption, the rapid advancement of digital technology has triggered significant changes in business, industry and even education. This transition presents both challenges and opportunities for the education sector. The evolving technological landscape has changed the way knowledge is accessed and delivered, with the concept of adaptive learning and online learning platforms reshaping the education landscape. This article aims to explore effective strategies for sustainable education in the disruptive era. Using a qualitative approach and a literature review, this research investigates the implications of the disruption era for education. The findings suggest that the education system must adapt to meet the demands of the changing times. Lifelong learning and the development of crucial skills have become essential for institutions and individuals to thrive and innovate in an uncertain future.